Interfacial reaction and dissolution behavior of Cu substrate in molten Sn-3.8Ag-0.7Cu in the presence of Mo nanoparticles - Arafat, M.M.; Haseeb, A.S. Md. Abdul; Johan, M.R. (2011)
Purpose In electronic packaging, when solid copper comes in contact with liquid solder alloy, the former dissolves and intermetallic compounds (IMCs) form at the solid-liquid interface. The purpose of this paper is to study the effect of the presence of molybdenum nanoparticles on the dissolution of copper and the formation of interfacial IMC. Design/methodology/approach Cu wire having a diameter of 250 mu m is immersed in liquid composite solders at 250 degrees C up to 15 min. Composite solder was prepared by adding various amount of Mo nanoparticles into the Sn-3.8Ag-0.7Cu (SAC) solder paste. The dissolution behavior of Cu substrate is studied for SAC and Mo nanoparticles added SAC solders. The IMCs and its microstructure between the solder and substrate are analyzed by using conventional scanning electron microscope (SEM) and field emission SEM. The elemental analysis was done by using energy-dispersive X-ray spectroscopy. Findings Generally, the dissolution of the substrate increases with increasing immersion time but decreases with the increase of the content of Mo nanoparticles in the solder. The IMC thickness increases with increasing the reaction time but Mo nanoparticles can hinder the growth of IMC layer. The presence of Mo nanoparticle is found to be effective in reducing the dissolution of copper into SAC solder. Originality/value The paper shows that molybdenum nanoparticles in liquid SAC solders have a prominent effect on the substrate dissolution rate and the interfacial IMC between the SAC solder and copper substrate.